Health Technology Assessment in Central America - García López, Flor E (2022)
Health systems in Central America are divided into different sectors, however, each sector has in common the provision of health services, this process links medical care with other actions such as diagnosis and therapy. Therapy as the main tool for disease prevention, healing and health maintenance, has evolved bringing with it innovation, which generally manifests itself with better health outcomes for patients, however, for some years the question has been raised about the value that these health outcomes represent at an individual, collective and health system level. To resolve this problem, health technology assessment has been incorporated into health systems as a tool to reduce uncertainty regarding the benefit to the user and the financing impact of the use of a new technology.